2022
DOI: 10.3389/fpsyg.2022.990565
|View full text |Cite
|
Sign up to set email alerts
|

Similar but different: High prevalence of synesthesia in autonomous sensory meridian response (ASMR)

Abstract: Autonomous sensory meridian response (ASMR) is a complex sensory-emotional experience characterized by pleasant tingling sensations initiating at the scalp. ASMR is triggered in some people (called ASMR-responders) by stimuli including whispering, personal attention, and crisp sounds (termed ASMR triggers). Since its inception, ASMR has been likened to synesthesia, but convincing empirical data directly linking ASMR with synesthesia is lacking. In this study, we examined whether the prevalence of synesthesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The insular cortex also integrates the internal senses, which recognize the conscious perception of bodily responses, such as visceral sensation and autonomic control, with external senses, such as emotion and empathy ( Uddin et al, 2017 ). This cross-sensory (decreased heart rate) and extrasensory (increased activity in somatosensory, motor, visual, and auditory cortices) activity is associated with the positive effects of ASMR on emotion via the autonomic nervous system ( Poerio et al, 2022 ). We believe that the present study provides support that this cross-activity response occurs because of preferred ASMR videos, although not tingling.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex also integrates the internal senses, which recognize the conscious perception of bodily responses, such as visceral sensation and autonomic control, with external senses, such as emotion and empathy ( Uddin et al, 2017 ). This cross-sensory (decreased heart rate) and extrasensory (increased activity in somatosensory, motor, visual, and auditory cortices) activity is associated with the positive effects of ASMR on emotion via the autonomic nervous system ( Poerio et al, 2022 ). We believe that the present study provides support that this cross-activity response occurs because of preferred ASMR videos, although not tingling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed phenomenon bears resemblance to synesthetic experiences, there appear to be distinct variations that differentiate it from traditional synesthesia. [ 51 ] Future studies on ASMR should consider exploring the phenomenon as a spectrum regarding how audio‐visual stimuli affect physiological regulation in individuals rather than relying solely on self‐reporting of tingling sensation. On the other hand, it would also be interesting to investigate whether such cross‐modal connections can be established in adulthood through repeated exposure to these stimuli, using a longitudinal approach.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Individuals with a SPS trait are easily overstimulated by external stimuli, and research has shown that their ASMR intensity is associated with SPS levels [8]. Synaesthesia is a phenomenon where a stimulus in one sensory modality elicits sensations in that modality and other modalities, and a higher prevalence of synaesthesia has been found among ASMR responders [1,6,9]. AIWS is a neurological condition known for distorted perception of the body and space, and it shares a distortion of time perception with ASMR.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of ASMR ranges from 23.5 to 28% [5,6]. The common ASMR triggers include auditory and audio-visual stimuli made with persons whispering, eating, and using objects to make sounds [2].…”
Section: Introductionmentioning
confidence: 99%